WHAT DETERMINES THE WATER QUALITY - B. Dalmacija (Journal of Engineering & Processing Management, 2010)
In natural waters as a highly complex environment, a different matter, regardless of whether they are natural water ingredients or substances which mature in water by man activity, are subject to one or several different processes. Physical, chemical or biochemical processes are determining finding shapes, behavior and fate of substances in the aquatic environment. Particularly important are: dissolution, adsorption, evaporation, photolysis, hydrolysis, oxidation-reduction, metabolic processes, and bioaccumulation. Depending on which processes are dominant in a given locality, what is the chemical composition of soil, biological activity, and human influence will determine quality of water, whether it is surface, underground or atmospheric. This paper presents the underlying processes that affect water quality. All processes are illustrated by examples.
Keywords: Water quality; surface water; underground water; sediment